A Pilot Study Investigating Differences in Sleep and Life Preoccupations in Chronic and Acute Insomnia - Samantha Man; Mark Freeston; Jason. G. Ellis; David. R. Lee (Sleep Medicine Research, 2013)
Background and Objective Theory suggests that during the transition from acute to chronic insomnia a shift in attention, from life events to sleep difficulties, occurs. The aim of this study was to examine whether this shift indeed exists, by measuring the frequency and type of preoccupations in acute and chronic insomnia. Methods Using a cross-sectional design, two groups [people with acute insomnia (n = 11) and chronic insomnia (n = 20)] completed a series of standardized and semi-idiosyncratic measures daily, over the period of one week. They also wore actigraphs to provide objective measures of sleep parameters. Results Findings suggest no differences in preoccupation between the two groups but show the acute insomnia group report significantly higher levels of perceived stress. Exploratory analysis suggests a reduction in scores on standardized measures across all participants between time 1 and time 2, and no differences on objectively measured sleep parameters. Conclusions Results indicate there is no difference between people with acute and chronic insomnia in level, and type, of reported preoccupation and that people with acute insomnia are as preoccupied during the day by both sleep and life events, as people with chronic insomnia. Limitations are discussed and future research questions are considered.